2006
DOI: 10.5694/j.1326-5377.2006.tb00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of methicillin‐resistant Staphylococcus aureus in a Queensland Indigenous community

Abstract: Objective: To determine the prevalence of community‐acquired methicillin‐resistant Staphylococcus aureus (CA‐MRSA) carriage and infection among children living in an Indigenous community in Queensland. Design, setting and participants: Swabs for culture of S. aureus were collected from the nose, throat and skin wounds of primary school children. Main outcome measures: MRSA carriage, antibiotic sensitivity, genotype, and presence of the virulence factor Panton–Valentine leukocidin (PVL); and epidemiological ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…The observed pattern of ST93 as a common cause of skin infections but an infrequent nasal colonizer is consistent with other colonization surveys in the NT and Queensland (Vlack et al , 2006; Brennan et al , 2013). In an impetigo treatment trial undertaken in children from NT Indigenous communities, nasal colonization with S. aureus was less common among those with S. aureus -related impetigo (13 %) compared to those without S. aureus impetigo (24 %) (Bowen et al , 2014), suggesting that there may not be a significant overlap of skin and nasal populations of S. aureus .…”
Section: Discussionsupporting
confidence: 90%
“…The observed pattern of ST93 as a common cause of skin infections but an infrequent nasal colonizer is consistent with other colonization surveys in the NT and Queensland (Vlack et al , 2006; Brennan et al , 2013). In an impetigo treatment trial undertaken in children from NT Indigenous communities, nasal colonization with S. aureus was less common among those with S. aureus -related impetigo (13 %) compared to those without S. aureus impetigo (24 %) (Bowen et al , 2014), suggesting that there may not be a significant overlap of skin and nasal populations of S. aureus .…”
Section: Discussionsupporting
confidence: 90%
“…The authors hypothesized that the result could be due to limited use of antibiotics in that population. Studies in North America and Australia, however, have shown that native and indigenous populations have been associated with a high risk of colonization and infection with CA-MRSA which may be related to many of these groups being disadvantaged, due to their association with low socio-economic status, crowded living conditions and frequent use of antibiotics [36, 37]. There have been reports of absolute resistance to penicillin and high percentage resistance to other antibiotics in milk from similar settings in central Uganda, hence risk of spread to humans through the food chain [27].…”
Section: Discussionmentioning
confidence: 99%
“…No Singleton 93 MRSA was found during the period of the surveys. PVL-positive ST93-MRSA-IVa (2B), also known as the Queensland clone, however, is an important Australian CA-MRSA that was originally found in a Caucasian population in Queensland in 2000 and has been reported in Indigenous people from Queensland 5,37 and the Northern Territory. 38 It is interesting that in an environment of high β-lactam use a methicillin-resistant variant of ST93-MSSA was not found in WA during these surveys.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia the first CA-MRSA, colloquially known as ‘WA MRSA’, was reported in 1993 in infected Indigenous people from remote communities in the sparsely populated Kimberley region of Western Australia (WA). 2 This was followed by reports of CA-MRSA from Indigenous people in the Northern Territory, 4 Queensland 5 and Central Australia. 6 …”
Section: Introductionmentioning
confidence: 99%